From dual to single umbilical artery: a case of umbilical artery thrombosis with hypercoiling and literature review - Ding, Weimin; Yan, Jiajia; Lin, Xinyu; Yan, Liangqi; Tao, Enfu (Frontiers in Medicine, 2025)
Umbilical artery thrombosis (UAT) is an extremely rare but severe obstetric complication associated with adverse perinatal outcomes, including fetal growth restriction (FGR), fetal distress, and intrauterine fetal demise. This case report highlights the diagnostic challenges of UAT and its potential misdiagnosis as a single umbilical artery (SUA). A 32-year-old woman with a history of uncomplicated vaginal delivery was initially misdiagnosed with SUA at 29 3/7 weeks of gestation. At 32 1/7 weeks, detailed ultrasound examination revealed a single umbilical artery, FGR, and hypercoiling. Following a multidisciplinary evaluation and administration of fetal lung maturation therapy, a cesarean section was performed at 32 3/7 weeks of gestation. Intraoperatively, the umbilical cord measured 90 cm in length (normal range: 35–70 cm) with over 50 coils and exhibited localized discoloration. A male neonate weighing 1,490 g (5th percentile for gestational age) was delivered with Apgar scores of 10/10 at 1 and 5 minutes. Postnatal pathological examination confirmed UAT with arterial occlusion and hypercoiling. The neonate was treated in the neonatal intensive care unit (NICU) for respiratory distress syndrome (RDS) and prematurity-related complications, achieving a favorable outcome with discharge at 27 days and normal developmental follow-up. This case underscores the diagnostic challenges of differentiating UAT from SUA and emphasizes the importance of meticulous prenatal ultrasound evaluation, particularly in cases of FGR. The hypercoiling observed in this case is exceptionally rare and may have contributed to the thrombotic event. Early recognition, timely intervention, and multidisciplinary management are critical to optimizing maternal and neonatal outcomes. This report also provides a comprehensive literature review on the etiology, diagnostic strategies, and management of UAT, highlighting the role of ultrasound and pathological examination in accurate diagnosis. The findings suggest that hypercoiling and abnormal cord length may be significant risk factors for UAT, warranting further investigation into their pathophysiological mechanisms and clinical implications.